Reproductive health and contraception use by Ukrainian servicewomen in the current war zone: a questionnaire survey - Burlaka , O.V.; Vahnier, V.O. (Medicni Perspektivi, 2021)
The aim of the study is to define awareness level and use of different contraception methods by servicewomen in the current armed conflict in the East of Ukraine. Between October 2018 and September 2019, 507 military women serving in the Joint Forces Operation Zone in eastern Ukraine and 100 civilian women from the frontline region participated in the questionnaire-based survey. The survey was focused on the knowledge and use of different methods of contraception and STI preventing by military women in conditions of armed conflict in Donbas. Servicewomen reported using of different methods of contraception in 48.3±4.3% of the cases, which is 1.5 times less than civilian women (RR=1.5; 95% CI: 1.2 – 1.7, p=0.001). Among those who reported using contraception, hormonal methods were chosen by 8.2±3.4% of active duty military women, which is two times less than by civilians (RR=2.1, 95% CI: 1.1-4.1, p=0.03). The low use of effective methods of contraception by active-duty servicewomen according to results survey is one of the reasons for the disruption of female reproductive health during military deployment. The primary reserve of preserving women’s health in the current war environment,besides access to modern contraceptives and counseling, is improving the education of military medics in the gender-specific issues of reproductive health and contraception.